Bulgarin’s “The Death of Lopatinsky” in Adaptations by Finnish Authors of the 19th Century - Mikhail Yu. Liustrov (Studia Litterarum)
The article explores the Swedish translation and poetic adaptations of F. Bulgarin’s “war story” “The Death of Lopatinsky,” published in Finland at the turn of the 1830s and 1840s. The article documents and explains the differences between the Swedish translations and the original Russian work. It also notes the reaction of the Finnish readership to the Swedish texts. The response to the relatively accurate translation of Bulgarin’s story published in the newspaper “Wasa tidning” (January 1839) was an article in “Borgå tidning” (May 1839), containing a truthful, in contrast to the Russian version, description of the death of Lieutenant Lopatinsky in September 1808. The article discusses Janne Lundmark’s poem “The Death of Lopatinsky, and the Voices at the Tomb,” which was published in Helsingborg in 1843. This poem is a poetic reworking of Bulgarin’s text and includes references to several characters from Scandinavian mythology, with the Houris being the most prominent. The article suggests that Lundmark indicates the eastern origin of the hero of the poem in this way. The article also notes that Valkyries and Houris often form a pair of “maidens of Paradise” in Swedish literature from the first half of the 19th century. Lundmark probably takes this into account. Finally, the article mentions that Lundmark’s poem is one of several works by Swedish-speaking authors from the 17th–18th centuries that are dedicated to the death of a hero.